SYNERGETIC IDEAS IN PEDAGOGICAL SYSTEMS SIMULATION - Victor M. Kureychik; Veronika I. Pisarenko (Открытое образование (Москва), 2016)
This article is devoted to consideration of the new approach in modern education system. This approach is connected to synergetics. Different points of view on synergetics as methodology of modern science are considered. Examples of synergetic principles application in humanitarian sciences are proposed. Synergetics in education, for education and of education are considered.